Effects of Inlet Velocity of a Bubble Column Reactor on the Fluid Flow Pattern for Biodiesel Production - RAJAH, SATHIS; nasir, nurul fitriah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Selecting wrong inlet velocity will decrease the efficiency and increase the production cost of biodiesel production since different velocity will have different flow pattern. Therefore, studying the effects of various inlet velocity on the fluid flow pattern using 3m/s, 4m/s and 5m/s in Bubble Column Reactor for transesterification reaction is essential in determining the best inlet velocity. CFD Simulation using ANSYS Workbench (Fluent) was carried out to determine and analyze the flow pattern after two specific Bubble Column Reactor, one with round obstacle and another with hexagonal obstacle was designed using SOLIDWORKS 2019. Bubble Column Reactor with round obstacle with inlet velocity of 3m/s had the best results in terms of flow pattern. Laminar flow has the best fluid flow compared to turbulent flow compared between these two designs. More types and size of obstacles should be studied in order to get a clear understanding on the effect of obstacles on the fluid flow pattern.